(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This scientific article examines the problems of migration between Turkey and the EU, the strategy of trade relations, the analysis of mutual investments on the example of the countries of Germany and Italy. In particular, the scientific work of scientists and political scientists on this topic was analyzed